How To Speak Russian With Easy Creative Oral Assignments As A Methode Of Developing Communication Competence (On The Example Of The Discussion Textbook) - Куца, Зоя (Didactics of the Russian language and the problems of translation for a foreign audience, 2020)
This article is an attempt to understand the role of communicative competence in foreign language teaching. This competence is considered by us as a complex of skills and abilities to successful communication and interaction between people. In the process of formation of communicative competence a communicator is required to be able to effectively express his thoughts and intentions through verbal and non-verbal means, taking into account adequate conditions and communicative situation. This material focuses on cognitive, behavioral and affective skills through which communication competence is acquired. The second part of the article presents a whole chain of creative tasks from the Discussion textbook, which develops communicative competence. Oral and language tasks are divided into three subgroups: 1) by using Internet resources, 2) examples of role-playing games, 3) oral tasks with visual content. Such tasks develop the students’ thinking processes, motivate them to communication process, develop the skills of navigating in a specific language situation, create the skills of correct choice of verbal and non-verbal instruments of communication.